Impact of Ethnic differences in the work force in Industrial Relations : A case study - Jain, Hem (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
At the light of the New Brunswick International Paper Company's experience, the author explores the effect of local conditions and of external economic and organizational factors on the process of accomodation. He also examines the degree to which all the parties involved are willing to reach accommodation in handling ethnic tension at plant level in this mill. An attempt is finally made to indicate the extent to which the finding of this case study might be applicable to other mills.